HUMAN CAPITAL DAN PERANAN PEMERINTAH DALAM PENDIDIKAN - NURJANAH, SITI (Jurnal Ilmiah Econosains, 2014)
Abstract Human Capital is the knowledge, skills and abilities that can be used to produce a professional service. Human capital for the company is owned by its employees collective ability to create ideas, innovations and solutions appropriate to contribute to the achievement of corporate goals. For individuals, human capital is the ability to be able to win the competition in the world to provide more value in financial terms for workers. The government's role in education is to protect them and provide opportunities for educational equity, acted as a partner, companion, facilitator, public servants and funders; protect citizens from the negative influence of outside parties, giving equal opportunity to learn for every citizen. Government as mandate Act of 1945 shall establish and conduct a national education system for all citizens of Indonesia. Keywords: Human capital, Role Of Goverment in Education